Fatigue Induced Changes in Muscle Strength and Gait Following Two Different Intensity, Energy Expenditure Matched Runs - Riazati, Sherveen; Caplan, Nick; Matabuena, Marcos; Hayes, Philip R. (Frontiers in Bioengineering and Biotechnology, 2020)
Purpose: To investigate changes in hip and knee strength, kinematics, and running variability following two energy expenditure matched training runs; a medium intensity continuous run (MICR) and a high intensity interval training session (HIIT). Methods: Twenty (10F, 10M) healthy master class runners were recruited. Each participant completed the HIIT consisting of six repetitions of 800 meters with a 1:1 work: rest ratio. The MICR duration was set to match energy expenditure of the HIIT session. Hip and knee muscular strength were examined pre and post both HIIT and MICR. Kinematics and running variability for hip and knee, along with spatiotemporal parameters were assessed at start and end of each run-type. Changes in variables were examined using both 2 x 2 ANOVAs with repeated measures and on an individual level when the change in a variable exceeded the minimum detectable change (MDC). Results: All strength measures exhibited significant reductions at the hip and knee (P < .05) with time for both run-types; 12% following HIIT, 10.6% post MICR. Hip frontal plane kinematics increased post run for both maximum angle (P < 0.001) and range of motion (P = 0.003). Runners exhibited increased running variability for nearly all variables, with the HIIT having a greater effect. Individual assessment revealed that not all runners were effected post run and that following HIIT more runners had reduced muscular strength, altered kinematics and increased running variability. Conclusion: Runners exhibited fatigue induced changes following typical training runs, which could potentially increase risk of injury development. Group and individual assessment revealed different findings where the use of MDC is recommended over that of P values.